2019
DOI: 10.1177/2331216519866029
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Sound of a Cochlear Implant: Evaluation of Different Vocoder Parameters by Cochlear Implant Users With Single-Sided Deafness

Abstract: Cochlear implantation in subjects with single-sided deafness (SSD) offers a unique opportunity to directly compare the percepts evoked by a cochlear implant (CI) with those evoked acoustically. Here, nine SSD-CI users performed a forced-choice task evaluating the similarity of speech processed by their CI with speech processed by several vocoders presented to their healthy ear. In each trial, subjects heard two intervals: their CI followed by a certain vocoder in Interval 1 and their CI followed by a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
(98 reference statements)
1
15
0
Order By: Relevance
“…In the present study, we have investigated two types of broadband stimuli (NBN and PSHC), which were 1/3-octave wide and had 36-dB per octave spectral slopes. These slopes are broadly consistent with previous vocoder studies that aimed to simulate the sound of CI (reviewed in Mesnildrey and Macherey, 2015; Karoui et al, 2019). However, it is likely that the spectral slope corresponding to that of the excitation spread of a CI electrode will vary across electrodes and across subjects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we have investigated two types of broadband stimuli (NBN and PSHC), which were 1/3-octave wide and had 36-dB per octave spectral slopes. These slopes are broadly consistent with previous vocoder studies that aimed to simulate the sound of CI (reviewed in Mesnildrey and Macherey, 2015; Karoui et al, 2019). However, it is likely that the spectral slope corresponding to that of the excitation spread of a CI electrode will vary across electrodes and across subjects.…”
Section: Discussionsupporting
confidence: 89%
“…PSHCs are pulsatile broadband stimuli that can simulate the broad spread of excitation and their pulse rate can be adjusted to minimize intrinsic modulations after auditory filtering (Mesnildrey et al, 2016). Furthermore, a recent evaluation in SSD subjects showed that speech processed by a vocoder using PSHC carriers was judged more similar to speech processed by the clinical CI processor than sine- or noise-vocoded speech (Karoui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Karoui et al (2019) assessed the similarity of three vocoders (sine, noise, and pulse-spreading harmonic complex) and three output maps (no upshift in frequency, two equivalent rectangular bandwidth [ERB] upshift, and four ERB upshift) to the sound of Cochlear Corporation CIs. The pulse-spreading harmonic complex was judged more similar to a CI than either sine or noise and either no shift or a two ERB shift were judged more similar than the four ERB shift.…”
Section: Preliminary Experimentsmentioning
confidence: 99%
“…A cochlear implant (CI) is a surgically implanted electronic device that provides a sense of sound for profound to total hearing loss patients. This neuroprosthesis bypasses the defunct cochlea by transferring acoustic vibrations of a sound into electric pulses of the electrodes to stimulate the auditory nerve, and subsequently the auditory cortex creating a somewhat synthetic sound perception of the environment [2].…”
Section: Introductionmentioning
confidence: 99%